The effect of the Seattle Police-Free CHOP zone on crime - Piza, Eric L. (Criminology & public policy, 2022)
Nightly confrontations occurred between protestors and officers outside of the Seattle Police Department's (SPD's) East precinct in the aftermath of George Floyd's murder. On June 8, 2020, the SPD abandoned the East precinct in an attempt to calm the situation. Following closure of the precinct, the Capitol Hill Occupation Protest (CHOP) took hold in the surrounding 6-block area. The CHOP occupation lasted until July 1, 2020. Over this time period, CHOP operated as an autonomous zone, with police officers not patrolling and generally not responding to calls for police service within the area. We used the microsynthetic control group method to analyze the effect of CHOP on crime during the 24-day occupation. Results indicate crime significantly increased in the CHOP zone, the encompassing two-block area, and the overall East precinct service area.